2015
DOI: 10.5812/pedinfect.26362
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of blaVEB-1 Beta-Lactamase Encoding Gene Among Extended Spectrum B-Lactamase Positive Wound Isolates of Pseudomonas aeruginosa

Abstract: Background: Pseudomonas aeruginosa is considered as a leading cause of nosocomial infections. Burn and wound infections are mainly caused by multidrug-resistant P. aeruginosa isolates. Drug resistance frequently occurs among nosocomial isolates and can usually resist a myriad of antibiotics such as novel β-lactam antibiotics. Detection of multidrug-resistant isolates could assist better drug administration. Objectives: The aim of this study was to detect Extended Spectrum Beta-Lactamases (ESBL) positive wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…About 0.3% of the total genes in P. aeruginosa are responsible for antibiotic resistance (14). Approximately 77% of ICU isolates were ESBL producers which is comparable with previous studies (15,16). Susceptibility to clavulanic acid is a diagnostic method.…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 70%
See 1 more Smart Citation
“…About 0.3% of the total genes in P. aeruginosa are responsible for antibiotic resistance (14). Approximately 77% of ICU isolates were ESBL producers which is comparable with previous studies (15,16). Susceptibility to clavulanic acid is a diagnostic method.…”
Section: Antibiotic Susceptibility Testsupporting
confidence: 70%
“…In the study by Shacheraghi et al in ESBL positive isolates, the prevalence of bla VEB-1 and bla PER-1 was 100% and 68.3%, respectively (18), but a low number (5.8%) of imipenem-resistant isolates contained bla PER-1 in another study. In a study by Davodian et al, among wound isolates the 90% and 88% were resistant to augmentin and cefpodoxime, 40% of them being bla VEB1 positive (15). Besides this, in our study, resistance to imipenem and meropenem was low (18.4 and 20%, respectively), suggesting that the low presence of carbapenemhydrolyzing enzymes in addition to class A enzymes.…”
Section: Discussionsupporting
confidence: 49%
“…With respect to bacterial resistance against the third generation cephalosporins, infected chronic wound isolates exhibited the highest rates of resistance ranging from 70% to 100% ( Fig 1 ) against cefixime (gramocef-0-400 ® ) and cefpodoxime (Ximeprox ® ). Findings from previous similar studies revealed comparable resistance of infected chronic wound isolates ranging from 87.6% to 100% resistance against cefpodoxime (Ximeprox ® ) and cefixime (gramocef-0-400 ® ) [ 17 , 18 ]. Therefore the therapeutic benefit of cefixime (gramocef-0-400 ® ) and cefopoxime 200mg (Ximeprox ® ) is extremely low to manage infected chronic wounds and continued use of these antibiotics will burden the patients with long hospital stays, high treatment costs, further delay of wound healing and development of severe invasive bacterial infections [ 19 ].…”
Section: Discussionmentioning
confidence: 96%
“…Difficulties in eradication of drug-resistant infections have been a critical issue in recent years. [2][3][4][5][6] Great therapeutic properties of aquatic sources including sterols, peptides, terpenes and nitrogen compounds, macrolides, acid-fat derivatives, prostaglandins, and other alkaloids have been revealed. 7 Bacterial infections cause many deaths annually.…”
Section: Enteric Pathogensmentioning
confidence: 99%